E. coli Is a Poor End-Product Criterion for Assessing the General Microbial Risk Posed From Consuming Norovirus Contaminated Shellfish - Sharp, Jasmine H.; Clements, Katie; Diggens, Mallory; McDonald, James E.; Malham, Shelagh K.; Jones, Davey L. (Frontiers in Microbiology, 2021)
The fecal indicator organism (FIO) Escherichia coli is frequently used as a general microbiological indicator to evaluate the success of the shellfish cleaning (depuration) process. To evaluate the robustness of this approach, the accumulation, retention, and depuration of non-pathogenic E. coli, pathogenic E. coli O157:H7 and norovirus GII (NoV GII) were evaluated using both culture-based and molecular methods after exposure of mussels (Mytilus edulis) to water contaminated with human feces. We simulated water contamination after a point-source release from a combined sewer overflow (CSO) where untreated wastewater is released directly into the coastal zone. All three microbiological indicators accumulated rapidly in the mussels, reaching close to maximum concentration within 3 h of exposure, demonstrating that short CSO discharges pose an immediate threat to shellfish harvesting areas. Unlike non-pathogenic E. coli, pathogenic E. coli bioaccumulated in the mussels. Depuration (72 h) in clean water proved partially successful at removing non-pathogenic E. coli from shellfish tissue, but failed to eradicate either pathogenic E. coli or NoV GII. We conclude that current EU standards for evaluating microbiological risk in shellfish are inadequate for protecting consumers against exposure to enteric viruses found in polluted marine waters.